Firefly wedding. 2 - Tachibana, Oreco (Tachibana, Oreco, Firefly wedding, 2025)
Satoko is kidnapped and imprisoned on an isle of prostitutes. To escape, she and Shinpei come up with a plan for her to pose as one herself, but there's one problem: Shinpei forbids her from letting another man touch her, vowing that he will be the only one to protect her. How can Satoko pull off a convincing performance with such a contradictory restriction in place?--